C9orf72 expansions in frontotemporal dementia and amyotrophic lateral sclerosis. Issue 3 (March 2015) - Rohrer, Jonathan D; Isaacs, Adrian M; Mizielinska, Sarah; Mead, Simon; Lashley, Tammaryn; Wray, Selina; Sidle, Katie; Fratta, Pietro; Orrell, Richard W; Hardy, John; Holton, Janice; Revesz, Tamas; et al.
Summary: C9orf72 hexanucleotide repeat expansions are the most common cause of familial frontotemporal dementia (FTD) and amyotrophic lateral sclerosis (ALS) worldwide. The clinical presentation is often indistinguishable from classic FTD or ALS, although neuropsychiatric symptoms are more prevalent and, for ALS, behavioural and cognitive symptoms occur more frequently. Pathogenic repeat length is in the hundreds or thousands, but the minimum length that increases risk of disease, and how or whether the repeat size affects phenotype, are unclear. Like in many patients with FTD and ALS, neuronal inclusions that contain TARDBP are seen, but are not universal, and the characteristic pathological finding is of dipeptide repeat (DPR) proteins, formed by unconventional repeat-associated non-ATG translation. Possible mechanisms of neurodegeneration include loss of C9orf72 protein and function, RNA toxicity, and toxicity from the DPR proteins, but which of these is the major pathogenic mechanism is not yet certain.